An uncommon fetal retention case: Ruptured ventral hernia in a sheep - PEKER, C.; UÇAR, E.H.; VAROĞLU, O.; ERDOĞAN, G. (Journal of the Hellenic Veterinary Medical Society, 2020)
A four-year-old pluriparous sheep was brought to our clinic with the complaints of mild anorexia and a wound on the ventral abdominal area, with part of a dead lamb protruding from this lesion. Clinical examination revealed that there was a fetal retention into the ruptured gravid uterine horn that was trapped within a ventral hernia. At herniorrhaphy after removing the dead fetus, strong connections between the uterine and abdominal wall and chronic scars/necrosed tissues were detected in the wound edges, which revealed the long time lapse between the unnoticed herniation-tearing and surgery. Although many ventral hernia cases have been reported in ovine pregnancies, the high maternal resilience in this ruptured hysterocele case, which had a two-week-old history at minimum, is clinically remarkable.